Modeling and assessment of pump impeller. (2020) - Iyankumar, R.; Mohanavel, V.; Vinoth, N.; Vinoth, T.
Abstract: Axial Flow pumps are elected based on the system requirements. Conventional design process takes a lot of time of the designer in calculations. Only experienced designers can do the design process successfully and produce required drawings accurately. In this competitive world, frequent changes in design are needed and also tailored according to customer requirements. The time taken for the design process should be reduced. This is very difficult to achieve in case of manual calculation process. The present work attempts to automate the design process of axial flow pump using computer aided design. The computer aided design tool was based on a Visual Basic program for hydraulic design calculations. The Hydraulic design of the impeller blade is based on Aerodynamic method. Mechanical design of the shaft was done and the diameter was found out using static analysis. The 3D model of the impeller was generated in Solidworks and imported into ANSYS environment with a view to do dynamic analysis. The 3D model of shaft and supporting elements such as bearing, coupling and hub was generated in ANSYS and dynamic analysis on this model was carried out for the design speed and stress values are found out at various sections of impeller. The analysis was also carried out for various speeds of the shaft and is finalized when the stress concentrations are minimum at all the sections. A procedure was developed starting with hydraulic design and completing with mechanical design of pump elements. Also a comparative study was carried out for various materials of the impeller such as brass, bronze and steel.